Pengaruh Kedisiplinan Bermeditasi Terhadap Frekuensi Kejadian Infeksi Saluran Napas Akut (ISPA) Komunitas Buddhis Dalam Usia Produktif Di STAB Nalanda: Pengaruh Kedisiplinan Bermeditasi Terhadap Frekuensi Kejadian Infeksi Saluran Napas Akut (ISPA) Komunitas Buddhis Dalam Usia Produktif Di STAB Nalanda - Henry Remanlay; R. Surya Widya; Lauw Acep (STAB Nalanda, 2021)
ABSTRACT ISPA is a disease that continues to be a burden to society, both in terms of the burden of illness suffered and from the financial side. at least 500 million ISPA incidents in the United States, and affect the economy of up to USD 40 billion per year. ISPA is an acute symptom characterized by coughing and fatigue. According to the 2013 RISKESDAS Indonesia, the incidence of ISPA in Indonesia from 2007 to 2013 was 25%. Handling that is done in dealing with ISPA is done with medication. ISPA in Traditional Chinese Medicine (TCM) is also called Ganmao. TCM treats ISPA, using acupuncture and herbal methods, while for prevention, exercises such as qigong and meditation are also applied. Meditation itself has been scientifically researched and recognized to be able to reduce stress and support health This study aims to examine the effect of meditation, especially Ānāpānasati, on the frequency of ARI incidence. The research